2018
DOI: 10.15171/bi.2018.15
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming of mouse fibroblasts into neural lineage cells using biomaterials

Abstract: Introduction: Induced neural stem cells (iNSCs) have the ability of differentiation into neurons, astrocytes and oligodendrocytes. iNSCs are very useful in terms of research and treatment. The present study offers an idea that biomaterials could be one of the tools that could modulate reprogramming process in the fibroblasts. Methods: Gelatin biomaterials were fabricated into 3 types, including (i) gelatin, (ii) gelatin with 1 mg/mL hydroxyapatite, and (iii) gelatin with hydroxyapatite and pig brain. NIH/3T3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…The cells might be passed through the neural stem cell (neural progenitor) state because the NIH/3T3 cells expressed the Klf4, a pluripotency marker which is significantly upregulated on the gelatin with hydroxyapatite and pig brain extract during the first week of the cell culture. The PI3K/Akt activation is involved in the early steps of the reprogramming process as it is increased in NIH/3T3-cell-cultured gelatin with hydroxyapatite and pig brain extract [89]. This evidence strongly supports that hydrogels can modulate transcription factors to cause reprogramming.…”
Section: Mechanotransduction and Epigeneticsmentioning
confidence: 55%
“…The cells might be passed through the neural stem cell (neural progenitor) state because the NIH/3T3 cells expressed the Klf4, a pluripotency marker which is significantly upregulated on the gelatin with hydroxyapatite and pig brain extract during the first week of the cell culture. The PI3K/Akt activation is involved in the early steps of the reprogramming process as it is increased in NIH/3T3-cell-cultured gelatin with hydroxyapatite and pig brain extract [89]. This evidence strongly supports that hydrogels can modulate transcription factors to cause reprogramming.…”
Section: Mechanotransduction and Epigeneticsmentioning
confidence: 55%
“…Amit et al [20] used a different mouse model of head and neck cancer to show that axons infiltrating a tumor from adjacent sensory nerves may be reprogrammed by tumor exosomederived miRNAs and acquire a sympathetic phenotype. Transdifferentiation of fibroblasts into neural precursors has been demonstrated in vitro [46,47], and some in vivo models have succeeded in transdifferentiating supporting astrocytes into functional neurons in mice [48]. Lastly, Mauffrey et al [36] suggested that DCX + neural precursors migrate from the brain into prostate cancers and generate adrenergic neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Kantawong et al 44 explored the potential of gelatin-hydroxyapatite-pig brain biomaterials in generating induced neural stem cells (iNSCs) from MEFs. iNSCs are not only capable of differentiating into neurons, but also into glial cells including astrocytes and oligodendrocytes.…”
Section: Review Biomaterials Sciencementioning
confidence: 99%
“…Indeed, culture on the gelatin materials upregulated astrocytic TF ( NFIA , NFIB , SOX9 ) expression even without viral TF infection. 44 Currently, astrocyte generation is slow in vitro , 48 which is a considerable limiting factor for studying neurodegenerative disease. Future studies could focus on further optimising gelatin-based substrates to shorten the differentiation period.…”
Section: Bionanomaterials and Epigenetics In Stem Cellsmentioning
confidence: 99%